(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article is devoted to the analysis of the technological process of cleaning fibrous materials from impurities and the possibilities of its computer modeling. The study examines the difficulties arising from the probabilistic nature of the interaction of fibrous mass particles with the working parts of cleaning machines. An overview of various approaches to modeling technological processes is presented, including geometric, dynamic, probabilistic (Markov), statistical, and simulation statistical models. A detailed analysis of the operation of the spiked drum and grid surface pair of the CL-P preliminary cotton cleaner is carried out. As a result of the impact action of the spikes, the acceleration of the cotton lump increases sharply and then decreases. It was found that along the X-axis, the acceleration initially becomes positive and then negative, which is explained by the transition from decelerated motion before the impact to accelerated motion after the impact. The paper presents differential equations describing the motion of a cotton lump, considering the impact force, air resistance, friction, and centrifugal force. It is shown that these equations cannot be solved analytically and require numerical integration using methods such as Runge-Kutta. The analysis of graphical dependencies shows that the friction coefficient and the rotational speed of the drum significantly affect the velocity of the lump and the path traveled. The obtained results allow for a more accurate description of the cleaning process and optimization of the design parameters of cleaning machines.